Individual Factors of Chinese Youth Scepticism toward TV Advertising - Jin, Yefan (2017)
The attitudes of young customers toward TV advertising is very important and has been studied decades because this generation has great buying potentials. As the development of technology and cultures, the tactics that advertisers use become increasingly diverse and persuasive, which leads to the increasing of defence and even scepticism of young adults toward TV advertising. To understand this type of advertising attitude is important because ad scepticism would result in inefficiency of ad information delivery. Therefore, there are much research that investigates the factors that influence ad scepticism. However, most of them focus on the influences of situational factors on adolescents, such as source credibility, advertising promises and so on, but the impact of individual factors over young adults, such as self-esteem, susceptibility to interpersonal influence and so on, is a gap. On the other hand, the Chinese customer is the research target of this study because of their much higher consuming potential than before, and unique social culture that could make the relationship between individual factors and ad scepticism different from foreign literature. The quantitative approach is employed to examine four individual factors that were investigated most by previous literature: knowledge about advertiser tactics, self-esteem, consumer susceptibility to interpersonal influence and age. The results of data analysis indicated that both knowledges about advertiser tactics and age are uncorrelated with ad scepticism of Chinese youth, while both self-esteem and consumer susceptibility are correlated with mistrust of advertiser tactics positively. Additionally, this study also finds consumer susceptibility is the mediation effect because self-esteem affects ad scepticism by affecting the variable consumer susceptibility. That is, people with high self-esteem who are susceptible to interpersonal interaction are more likely to mistrust the tactics of advertiser than those who are unsusceptible to interpersonal interaction. This finding is totally different from previous literature. This research suggests that Chinese customers are more willing to trust advertising information from familiar people instead of official ad sources, so marketers should pay attentions on the interpersonal marketing strategy, such as word-of-mouth marketing. Also, it inspires advertisers to consider the cultural differences between different countries when considering to apply the foreign research to Chinese markets.